2016
DOI: 10.1590/1413-785220162402149097
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Martin-Gruber Anastomosis

Abstract: Objective: This paper reports the incidence, origin, course and anatomical relationships of intramuscular Martin-Gruber anastomosis. Methods: Anatomical dissection of 100 limbs from 50 adults cadavers was performed. The intramuscular Martin-Gruber anastomosis was found in five forearms, three in the right and two in the left side, one was bilateral. All communication were located between the anterior interosseous nerve and the ulnar nerve. Conclusion: The purpose of intramuscular Martin-Gruber anastomosis, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The DorBUN provides cutaneous innervation to dorsal medial surface of the hand and digits [49,59]. At the wrist the main body of the Ulnar nerve gives off small variable palmar cutaneous branches, which supply the skin of the hypothenar eminence [12,19,49,59].…”
Section: Ulnar Nerve -Normal Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…The DorBUN provides cutaneous innervation to dorsal medial surface of the hand and digits [49,59]. At the wrist the main body of the Ulnar nerve gives off small variable palmar cutaneous branches, which supply the skin of the hypothenar eminence [12,19,49,59].…”
Section: Ulnar Nerve -Normal Anatomymentioning
confidence: 99%
“…The MGA is formed in the forearm by an anastomosis between either the Anterior Interosseous Nerve or the main body of the Median nerve, to the Ulnar nerve [12,13,26,45,53,70]. The nerve axons start in the proximal Median nerve and cross the forearm to join the distal Ulnar nerve [70].…”
Section: Martin Gruber Anastomosis (Mga)mentioning
confidence: 99%
“…[3][4][5][6][7][8] In S. leucopus, intra-and interspecific variations have been reported in the m. brachioradialis 9 and the m. flexor digitorum lateralis, 10 but there are no variations in nerves, and the innervation to the forearm muscles, which is important for diagnosis and treatment of nerve damage. 11 Thus, the main objective of this investigation was to describe the gross anatomy of this muscle in an arboreal quadruped such as S. leucopus and report variations in its nerve supply.…”
Section: Introductionmentioning
confidence: 99%
“…5,23,25,26 Conversely, a patient may present with symptoms of carpal tunnel syndrome, but show negative findings with regard to Tinel and Phalen tests, due to ulnar nerve compression at the elbow. 8 The intramuscular MGA subtype mentioned previously, found in 5% of total limbs (n = 100) in the study by Caetano et al, 8,19 is clinically relevant in and of itself. This branch penetrates the flexor digitorum profundus muscle, potentially serving as a location of nerve compression.…”
Section: Martin-gruber Anastomosismentioning
confidence: 75%
“…Located in the forearm, MGA has a prevalence of 19.5% as estimated by the meta-analysis of 41 studies (n = 6,409 upper limbs) conducted by Roy et al 7 Caetano et al 8 observed a prevalence as high as 27% using an anatomical dissection method, demonstrating the degree of variation that may be possible. In the same study, Roy et al further showed that MGA is more commonly unilateral and on the right side, in agreement with other studies.…”
Section: Martin-gruber Anastomosismentioning
confidence: 99%